PEMBELAJARAN BERBASIS STEM (SCIENCE. TECHNOLOGY, ENGINEERING, MATHEMATICS) PADA SISWA MADRASAH ALIYAH UNTUK MENINGKATKAN 21st CENTURY SKILLS - agustin, ina; Rakhma Widiyanti, Ifa Seftia (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2022)
The purpose of this research was to apply STEM-based learning to improve the 21st Century Skills of Madrasah Aliyah students. The subject of study is class X MA Nurul Huda Kragan Rembang, Central Java. The procedures research consists of the preparation, implementation, and presentation stages. The learning design used in this study is a quasi-experimental design with a nonequivalent control group design model. The STEM ability profiles studied are 1) Critical Thinking (providing connections between various scientific knowledge learned by students and real-life problems); 2) Creative (directing students to apply their knowledge through an engineering design process to create a technological solution to a problem); 3) Collaborative (proving that problem solving is possible by pairing machines, this modeling is then tested and the results will be evaluated whether the problem solving solution model is effective for solving the problem or not, if it is deemed ineffective then the design of the problem solving model is improved) t; 4) Communicative (able to calculate the impact that occurs when using the technology that has been made). After applyed STEM-based learning, the Critical Thinking skills of MA Nurul Huda Kragan students increased by 27.69%, Creative abilities increased by 12.00%, Collaborative abilities increased by 17.23%, and Communicative abilities increased by 36.92%.